The Empirics of Economic Growth Over Time and Across Nations: A Unified Growth Perspective - Matteo Cervellati; Gerrit Meyerheim; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
This research develops an expanded unified growth theory that incorporates the endogenous accumulation of physical capital, population, human capital, and technology. The model incorporates a complementarity between physical capital and human capital and can be extended to a multi-country setting with international technology diffusion. The analytical characterization of the mechanisms behind the observed patterns of long-run growth and comparative development delivers a consistent explanation for a large set of seemingly unrelated empirical facts. A quantitative multi-country version of the model matches various empirical regularities of long-run growth dynamics and comparative development patterns that have previously been studied in isolation. The findings also shed new light on the role of the demographic transition for convergence patterns, the specification of cross-country growth regressions, technology spillovers, and the secular stagnation debate.
Keywords: O47; O11; O15; E24; 330; unified growth; long-run development; demographic transition; secular stagnation